Logging identification of karstified Jurassic conglomerate aquifer in the Zhuxianzhuang coal mine: implications for water abundance heterogeneity and mining risk mitigation - Guanyu, Zhu; Bo, Jiang; Ming, Li; Yu, Song; Guoxi, Cheng (Frontiers in Earth Science, 2025)
The Jurassic conglomerate aquifer in the coal seam roof of Zhuxianzhuang Coal Mine in the Huaibei Coalfield exhibits significant karst and water-rich heterogeneity, and its geological patterns remain poorly understood. This study systematically investigates the lithology, stratigraphy, structural characteristics, karst features, and hydrogeological conditions of the Jurassic conglomerate aquifer. The conglomerate composition primarily consists of limestone, which undergoes intense and differential karstification and weathering. According to the fluctuation response characteristics of logging curves with different karst developments, a conglomerate aquifer karst logging identification model was constructed using apparent resistivity, artificial gamma, caliper, and acoustic time-difference as the key indicators. The aquifers were vertically classified into three types: intact section, relatively intact section, and broken section. Based on this classification and geological law, the vertical zonation and planar zonation characteristics were investigated. The conglomerate aquifers were further divided into four vertical development types: weathering crust type, karst type, composite type, and intact type, as well as six karst development planar zones. Influenced by the geological conditions of syncline structure, surface weathering and groundwater runoff, the overall distribution pattern of conglomerate aquifers demonstrates a progression from shallow to deep, transitioning from weathering crust types to composite, karst, and intact plane combinations.